Xanthogranulomatous Pyelonephritis as a Complication of Obstructive Uropathy: Clinical Case - Villanueva-Pinelo, Jairo David; Michel-Ramirez, José Manuel; Flores-López, Alejandro Alberto; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Described in 1916 by Schlagenhaufer, Xanthogranulomatous Pyelonephritis (XGP) is an uncommon type of chronic infectious pyelonephritis that evolves with a suppurative process and severe impairment of the renal function. Adult women and seniors are most affected and are commonly associated with urinary tract obstruction and infection. Children are rarely affected, as well as bilateral impairment. Clinical Case: A 54-year-old female comes to the emergency room with right lower back pain, nausea, vomiting, and fever. She denies chronic degenerative diseases and refers to herself as a carrier of right renal lithiasis. Surgical History: open cholecystectomy 20 years ago, two cesarean sections 33 and 23 years ago. The current condition began two months ago with pain in the right lumbar region, accompanied by intermittent fever during the day, presenting partial improvement with analgesics and antipyretics. In the last 24 hours, he presented vomiting of gastro biliary content on four occasions and increased lumbar pain. Upon admission, we performed abdominopelvic tomography, in which an enlarged right kidney was observed, with extensive loss of morphology with ectasia throughout the collecting system that extends to the UP junction with the presence of a 20x20 mm stone with a density of 800 HU inside, ureter with slight ectasia along its entire length, identifying the bear claw sign. Due to tomographic findings with obstructive uropathy and in the presence of data of systemic inflammatory response, he decided to perform diversion of the urinary tract with a double J ureteral catheter without success despite several attempts. Discussion: The precise pathophysiology remains incompletely understood. However, given the observed associations, the combination of obstruction and infection is presumed to be the primary initiators, resulting in interstitial pyelonephritis and a subsequent chronic granulomatous immune response that fails to eradicate the inciting agent.